Symplastic Transport in Ipomea tricolor Source Leaves : Demonstration of Functional Symplastic Connections from Mesophyll to Minor Veins by a Novel Dye-Tracer Method - Madore, Monica A. (1986)
A novel method for the delivery of the fluorescent dye Lucifer Yellow CH to the cytosol of a source leaf mesophyll cell was devised which utilized a preencapsulation of the dye in phospholipid vesicles (liposomes). The liposomes were easily injected into the vacuoles of leaf cells of Beta vulgaris or Ipomea tricolor, where fusion with the tonoplast resulted in the release of the dye into the cytosol. Subsequent cell-to-cell movement of the dye was readily followed by fluorescence microscopy. Using this liposome technique symplastic continuity from the the mesophyll to the minor veins of the source leaf of Ipomea tricolor was demonstrated. This agreed with ultrastructural studies which demonstrated the presence of plasmodesmata between all cells from the mesophyll to the minor veins. The symplastic movement of dye from the injected mesophyll cell to the minor veins was unaffected by pretreatment of the leaf tissues with 2 millimolar p-chloromercuribenzenesulfonic acid. Pretreatment of the leaf tissues at alkaline pH (3-[N-morpholino] propanesulfonic acid-KOH, pH 8.0) had no apparent effect on dye movement between adjacent mesophyll cells but inhibited the movement of dye into and along the minor veins. Thus, although there were no apparent barriers to symplastic solute movement in this leaf, symplastic barriers could be imposed by the experimental conditions used.